A Study of Teachers' Attitudes Toward Teaching for Creativity in Relation to Their Professional Development - AlAshour, Hussain Saleh Ahmed; AlHindal, Huda Soud (Journal of Educational and Psychological Sciences, 2020)
The main aim of this research was to investigate the relationship between secondary teachers' attitudes toward teaching for creativity and their professional development via the correlational-descriptive method. The sample consisted of 49 Saudi secondary school teachers who were selected randomly from the Qatif's secondary schools of KSA. The instrument of this study was developed by Wadaani (2015), which consisted of 16 items on a five-point Likert scale. One hypothesis was established to examine the correlation of the research variables via the descriptive analysis and the multiple regression analysis The findings of this study show that there is a significant positive relationship between teachers attitudes toward teaching for creativity and their professional development, but this relationship is weak based on its effect size, which is just 16.03% since R (square) is at 0,1603, indicating that teachers' attitudes toward teaching for creativity are partially related to their professional development and it may be possible to predict it. This study recommended that teachers should focus on their development via the training programs and these training programs should be designed in a way that encourages them to participate and react by means of providing incentives during the training.
Keywords: Teaching for creativity; Professional development